Design and Testing of a Wearable System for Monitoring Car Drivers - Julien Moinard; Marco Ceccarelli; Matteo Russo (Applied Sciences)
The increasing concern over driver safety has led to the development of various monitoring systems aimed at assessing the physiological state of drivers. This paper presents the design development and testing of a wearable system that monitors key physiological indicators such as heart rate, skin conductance, and movement to evaluate whether the driver’s behavior is aggressive. The system integrates multiple sensors to provide real-time data on the driver’s state. Our objective is to enhance driver safety by detecting aggressive driving behavior through continuous monitoring. This paper covers the conceptual design, performance analysis, and testing layout of the system. Results indicate the system’s effectiveness in detecting changes in physiological states, suggesting its potential for improving road safety and its potential for practical implementation.